Chinese traditional ink painting characters as a new concept of visual communication design - Wenyu, Wang (2023)
The significance of Chinese traditional ink painting as a new concept in visual communication design has been challenging to meet aesthetic needs as well as its information function. The development of a new visual communication design should keep up with the current trends so that the visual communication design can get rid of the limitations based on the traditional design in the context of its layout, concept, and spiritual value. This research aimed to investigate the Chinese traditional ink painting character that can be explored into a new concept of visual communication design for better aesthetic appearance and information function. The methodology for this research included a literature review and data collection through the survey. A survey conducted involved several experts such as artists, designers, industry practitioner, and scholars that knowledgeable in Chinese traditional ink painting. The results identified ten (10) most valuable characters of Chinese traditional ink painting that can be explored into a new concept in Chinese visual communication design. The conclusion of this study is to put forward a new method, namely, CTIPC based on VCDE, which integrates visual communication elements with traditional Chinese ink figures, as a new concept of Chinese visual communication design, with better aesthetic appearance and information function. Validation through user conducted to provide better understanding and prove the value of Chinese traditional ink painting characters as a new concept in Chinese visual communication design.